0804 Enhanced Drug-Induced Sleep Endoscopy: Distinguishing Central from Obstructive Apneas. (25th May 2022) - Cheong, Crystal; Schwartz, Alan; Seay, Everett; Mora, Jorge; Thaler, Erica; Dedhia, Raj
Abstract: Introduction: Drug-induced sleep endoscopy (DISE) is a useful tool for assessing upper airway collapse in patients with obstructive sleep apnea (OSA) and frequently influences surgical plans. The standard DISE setup of an endoscopic tower with flexible bronchoscope is adequate for visualizing collapse configurations, but endoscopic findings do not always correlate with actual respiratory physiology. We describe our enhanced clinical DISE setup incorporating nasal flow and respiratory effort measurements, which facilitates differentiation between central and obstructive events. Central sleep apnea was detected in two patients who were originally diagnosed with OSA and underwent DISE during hypoglossal nerve stimulation candidacy workup. Report of Cases: Case 1 is a 58-year-old male with cardiomyopathy, atrial fibrillation and congestive heart failure who was diagnosed with moderate OSA on a home sleep apnea test. He was PAP intolerant due to claustrophobia. DISE during baseline breathing revealed complete anteroposterior collapse at the palate, tongue base and epiglottis. However, central apneas with Cheyne-Stokes breathing were noticed when positive airway pressure (PAP) was applied. A subsequent polysomnogram revealed severe sleep apnea which was primarily central in nature with Cheyne-Stokes breathing and OSA. He declined retrying PAP and opted for phrenic nerve stimulation. Case 2 is a 48-year-old male with a history of aortic valve repair, hypothyroidism, atrial fibrillation provoked by excessive thyroxine, hypertension and moderate OSA diagnosed on several polysomnograms. He had been treated previously with nasal and palatal surgery, oral appliances and PAP. DISE revealed complete anteroposterior collapse of the palate and tongue base, but also central apneas during baseline breathing and at low PAP levels. Polysomnogram performed following his DISE confirmed central sleep apnea which was positional in nature. He chose to undergo positional therapy instead of PAP or phrenic nerve stimulation. Conclusion: The nasal flow and respiratory effort measurements included in our enhanced DISE setup enable the sleep surgeon to recognize the absence of respiratory effort even in the face of soft tissue collapse observed on videoendoscopy. These cases demonstrate the ability of propofol to preserve pathophysiologic mechanisms of sleep apnea (i.e. central versus obstructive), and underscore the importance of DISE as a diagnostic tool prior to sleep surgery. Support (If Any): NIH 1R01HL144859-01